Clustering Kabupaten/Kota di Provinsi Papua Berdasarkan Produk Domestik Regional Bruto Menurut Lapangan Usaha Menggunakan Single Linkage dan K-Medoids - Allo, Caecilia Bintang Girik (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2024)
Gross Regional Domestic Product (GRDP) using the production approach represents the total value added from goods and services produced by different sectors within a specific region over a defined timeframe. There are 17 business sectors used to obtain the GRDP. The growth rate of GRDP in Papua is decrease in 2023. The growth rate is only 3,44%, whereas the previous year it reached 4,11%. An analysis is needed to assist the government to enhance the GRDP in Papua. Clustering method can group districts/cities that have similar characteristics. The aims of this article is to determine the best method for clustering districts/cities in Papua using GRDP data. Single Method and K-Medoids is used in this article. Based on silhouette coefficients, Single Methods is better than K-Medoids to clustering districts/cities in Papua. Based on criteria of silhouette coefficients, number of clusters formed is three.